Disease progression in HIV-infected patients treated with stavudine vs. zidovudine. - Justice, Amy C; Stein, Daniel S; Fusco, Gregory P; Sherrill, Beth H; Fusco, Jennifer S; Danehower, Susan C; Becker, Stephen L; Hansen, Nellie I; Graham, Neil M H (Journal of clinical epidemiology, 2004)
This prospective, observational study compared disease progression and death in HIV-1 patients treated with stavudine vs. zidovudine in the Collaborations in HIV Outcomes Research/U.S. (CHORUS) cohort.
Keywords: Acquired Immunodeficiency Syndrome; Anti-HIV Agents; Antiretroviral Therapy, Highly Active; Databases, Factual; Disease Progression; Disease-Free Survival; Follow-Up Studies; HIV Infections; HIV Wasting Syndrome; Humans; Proportional Hazards Models; Prospective Studies; Reverse Transcriptase Inhibitors; Stavudine; Zidovudine